PENGARUH KETERAMPILAN WIRAUSAHA DAN PENGALAMAN USAHA TERHADAP KEBERHASILAN KEWIRAUSAHAAN - Keke Arnesia Iskandar; Arief Syah Safrianto (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2020)
The purpose of this study was to determine the effect of entrepreneurial skills and business experience on entrepreneurial success (Case study of the food and beverage sector in Bojong Rawalumbu village). The number of population used was 158 taken from the food and beverage sector entrepreneurs in the Bojong Rawalumbu village and the number of samples used in this study was 97 respondents. This research is a quantitative study, using multiple linear regression analysis. The results of this study were obtained simultaneously showing a positive and significant effect of entrepreneurial skills on entrepreneurial success and simultaneously business experience had a positive and significant effect on entrepreneurial success. Partially, there is a positive and significant influence of entrepreneurial skills and business experience on entrepreneurial success. And there are suggestions given, namely in the Bojong Rawalumbu village so that entrepreneurs in the food and beverage sector are more concerned with holding routine skills development training programs in order to gain more business experience, to achieve entrepreneurial success.